2010
DOI: 10.1177/1077546309103423
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Vibrations in Flexible Structures Using Supplementary Absorbers: Dynamic Optimization

Abstract: We propose a novel strategy for the optimal design of supplementary absorbers that warrant confinement with and without suppression of vibrations in flexible structures. We assume that the uncontrolled structure is sensitive to vibrations and that the absorbers are the elements where the vibrational energy is to be transferred. The design of these absorbers is formulated as a dynamic optimization problem in which the objective function is the total energy of the uncontrolled structure. The locations, masses, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Substituting Equation (17) into Equation (29) yields the same set of equations. This indicates that minimizing the power dissipated by the primary damping is equivalent to maximizing the power dissipated by the absorber damping for the same set of µ and ζ p .…”
Section: Optimization Of a Non-traditional Tmd For Vibration Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Equation (17) into Equation (29) yields the same set of equations. This indicates that minimizing the power dissipated by the primary damping is equivalent to maximizing the power dissipated by the absorber damping for the same set of µ and ζ p .…”
Section: Optimization Of a Non-traditional Tmd For Vibration Suppressionmentioning
confidence: 99%
“…The following literature review will focus on simultaneous VS and EH using TMD. Ouled Chtiba et al [17] optimized the locations, masses, stiffnesses, and damping coefficients of a set of TMDs to minimize the total energy of the primary structure. Later, they [18] proposed an optimal design for a set of TMDs incorporated with piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…In Viana et al (2008) uses the ant colony optimization technique to arrive at the optimal parameters of a vibration absorber. In Pennestri (1998) applied a Chebyshev's min-max criterion for finding the optimal damper parameters, and others numerical studies based on minimax optimization are reported in (Ouled Chtiba et al (2010b), Randall et al (1981), Brown and Singh (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Cho [7] investigated dynamic characteristics of a simply supported beam traversed by multiple moving loads and a practical scheme for suppressing the resulting resonant or excessive vibration by using a damped absorber. In [8] Chtiba and his colleagues have proposed a new strategy for the optimal design of supplementary absorbers that warrant confinement with and without suppression of vibration in flexible structures. In [9] Vestroni et al studied the pedestrian-induced vibrations in suspension footbridges via multiple tuned mas dampers.…”
Section: Introductionmentioning
confidence: 99%